Tlingit materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986
One item relating to the Tlingit language has been identified in the C. F. Voegelin Papers. It consists of a Tlingit folder located in Subcollection II, Series II. Research Notes, Subseries II. Na-Dene.